Definition of sinonasal and otological exacerbation in patients with primary ciliary dyskinesia: an expert consensus - Myrofora Goutaki; Yin Ting Lam; Andreas Anagiotos; Miguel Armengot; Andrea Burgess; Raewyn Campbell; Mathilde Carlier; Nathalie Caversaccio; Neil K. Chadha; Berat Demir; Sinan Ahmed D. Dheyauldeen; Onder Gunaydin; et al. (ERJ Open Research)
Background Recurrent infections of the nose, sinuses and ears are common problems for people with primary ciliary dyskinesia. While pulmonary exacerbations in primary ciliary dyskinesia are defined, there is no definition for ear-nose-throat exacerbations, a potential outcome for research and clinical trials. Methods We set up an expert panel of 24 ear-nose-throat specialists, respiratory physicians, other healthcare professionals and patients to develop consensus definitions of sinonasal and otological exacerbations in children and adults with primary ciliary dyskinesia for research settings. We reviewed the literature and used a modified Delphi approach with four electronic surveys. Results Definitions for both sinonasal and otological exacerbations are based on a combination of major and minor criteria, requiring three major or two major and at least two minor criteria each. Major criteria for a sinonasal exacerbation are 1) reported acute increase in nasal discharge or change in colour, 2) reported acute pain or sensitivity in the sinus regions and 3) mucopurulent discharge on examination. Minor criteria include reported symptoms, examination signs, doctor's decision to treat and improvement after at least 14 days. Major criteria for the otological exacerbation are 1) reported acute ear pain or sensitivity, 2) reported acute ear discharge, 3) ear discharge on examination and 4) signs of otitis media in otoscopy. Minor criteria are reported acute hearing problems, signs of acute complication, and doctor's decision to treat. Conclusion These definitions might offer a useful outcome measure for primary ciliary dyskinesia research in different settings. They should be validated in future studies and trials together with other potential outcomes, to assess their usability.